(untitled) (Research, Society and Development, 2023)
Objective: to reflect on stress in Primary Health Care (PHC) workers in the scenario of the COVID-19 pandemic, in the light of Betty Neuman’s Systems Model Theory; Methodology: This is a Theoretical Essay based on a Narrative Review, on the main predictors for the development of stress in PHC workers, carried out from July to November 2022. Results: 10 articles were selected to compose the training of this research. The selected articles highlighted that the main predictors that contribute to the development of stress in primary health care workers in the context of the COVID-19 pandemic are organizational, individual, work and social factors. Final Considerations: showed a growing trend of stress in primary health care professionals during the COVID-19 pandemic, as the mental health of these professionals has been a major concern because psychological distress raises alerts about the need for intervention, as the professionals are increasingly exposed to chronic stressors.